Pengaruh Sertifikasi Halal dan Kinerja Pemasaran terhadap Keberhasilan Usaha Warung Makan di Kota Bogor - Alfarisi, Mochamad Bimo; Sarma, Ma'mun; Sembiring , Indra Refipal (Jurnal Manajemen dan Organisasi, 2025)
The increasing public awareness of consuming halal food products created a large market potential for culinary businesses, especially food stalls. Bogor City has experienced fluctuating and declining growth in the number of food stalls, which may be due to increasingly intense competition in this sector. Meanwhile, the number of halal certified food stalls continued to grow significantly. Having a halal certificate could be one way for businesses to survive and gain a competitive advantage. Marketing performance was also an important aspect that needed be considered as a strategy to strengthen business competitiveness, which ultimately leads to sustainable business success. This study aimed to analyze the effect of halal certification and marketing performance on the business success of food stalls in Bogor City. This study involved 87 food stalls business actors who had obtained halal certification from BPJPH. The data were collected using a non-probability sampling method through questionnaire distribution. Data analysis was conducted using Structural Equation Modeling Partial Least Square (SEM-PLS). The findings of this study showed that halal certification had a positive and significant effect on business success, as well as a positive and significant effect on marketing performance. Marketing performance had a positive and significant effect on business success. Marketing performance also plays a partially mediating role in the relationship between halal certification and the business success of food stalls in Bogor City.